The impact of trust and social network on employee knowledge sharing capabilities / Azwan Ahzran Perman, Saiful Zizi Jalil and Zuraidah Zaaba - Perman, Azwan Ahzran; Jalil, Saiful Zizi; Zaaba, Zuraidah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
This research is from a knowledge management domain. It looks into employees’ knowledge sharing capabilities in selected private and public institutions in Kota Kinabalu, Sabah. The focused was on the impact of trust and social network on employee knowledge sharing capabilities. The questionnaires were distributed to 5 public and private institutions in Kota Kinabalu. For confidentiality issue, the name of the organization was not disclosed and to respect the request of the organizations. Statistical analysis was used to analyse 127 respondents. These analyses applied multiple regression analyses to test the relationships of the variables. It was argued that at the early development of the research, both variables had a positive relationship with the dependent variable. The result showed, trust and social network has a positive relationship among employees’ knowledge sharing capabilities. The research implied that trust and social network should be considered by the management of the private and public sector to develop and improve the overall employee knowledge sharing capabilities in their organization. Therefore, policies or programs initiated by any organizations should reflect the usage of these two variables to ensure the proper effectiveness of the employees in sharing knowledge for the benefit of the organization in the short and long term.